2009
DOI: 10.1007/978-1-60761-350-3_12
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of PON1 Activity in Adult and Childhood Obesity and Its Relation to Adipokine Levels

Abstract: Obesity as a pathogenic disorder is a predisposing factor for cardiovascular diseases and shows an increasing incidence in the industrialized countries. Adipokines such as leptin, adiponectin and resistin have a great impact on the development of atherosclerosis in obesity. Elevated levels of leptin have been found to be atherogenic whereas decreased levels of adiponectin have been proved to be anti-atherogenic in recent studies. The exact role of resistin in the process of atherosclerosis has so far remained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 41 publications
2
23
0
3
Order By: Relevance
“…Our data is consistent with fi ndings of other studies Seres et al, 2010] that showed that adiponectin proved to be an independent factor of PON1 activity in both childhood and adult obesity.…”
Section: Resultssupporting
confidence: 93%
“…Our data is consistent with fi ndings of other studies Seres et al, 2010] that showed that adiponectin proved to be an independent factor of PON1 activity in both childhood and adult obesity.…”
Section: Resultssupporting
confidence: 93%
“…In addition, it was demonstrated that a PON1 variant, PON2, attenuates the accumulation of triglycerides in mouse macrophages by reducing intracellular oxidative stress and inhibiting diacylglycerol acyl transferase (11). These previous results explain another previous report in which serum PON1 activity was shown to be negatively related with obesity (12). Consistently, the results of this study showed that PON1, an ABS-specific protein, may have an anti-adipogenic effect by decreasing oxidative stress during the differentiation of preadipocytes.…”
Section: Discussionsupporting
confidence: 90%
“…2 with an oval) were identified as peptides derived from immunoglobulins, which are supposed to be involved in immune responses. However, two protein spots were identified to as alpha-2-macroglobulin (A2M) and paraoxonase/arylesterase 1 (PON1), which were previously reported to suppress adipocyte differentiation (9,11,12). Therefore, A2M and PON1 were further analyzed with ABS, FBS, and fractionated serum proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Obesity, in particular, is considered a condition of chronic oxidative stress[19]. Data on the relationship between PON1 and obesity, especially in children, are limited[20]. In adults, a few small studies have reported a trend of lower PON1 activity in obese versus normal weight individuals[21], [22], [23].…”
Section: Introductionmentioning
confidence: 99%